Controle genético da resistência ao vírus do mosaico do trigo em Triticum aestivum L. Thell - Barbosa, Marta Martins (1996)
In the world, in ideal conditions for development of Soilborne Wheat Mosaic Virus (SBWMV) it may cause up to 50% yield losses in wheat fields and over 75% in experimental areas. In Southern Brazil this virus occurs in an endemic way and causing up to 50% yield reduction in wheat fields grown with susceptible cultivars. The most effective and only practical mean of controlling SBWMV is the use of resistant cultivars. However, the inheritance of resistance is not fully understood. Therefore, the objective of this study was to elucidate the mode of inheritance of field reaction to SBWMV. The resistant cultivar EMBRAPA 16 was crossed with the susceptible cultivars BR 23 and IAC 5-MARINGÁ. The parentals, F, and F2 families and backcrossed Fi families were tested under natural conditions in the field, in two areas with different leveis of SBWMV infestation. Plants were assessed visually and individually for symptom severity 45 days after seeding and rated on a scale from 0 to 5, where 0 = no symptoms and 5 = severily affected by mosaic, stunting and/or rosetting. Data analyzed showed values of broad sense heritability between 43% and 74% for both crosses. Additive variance values were insignificant indicating the presence of dominance with values varying respectively from 0.59 to 1.42, considering the smaller estimated values of environmental variance. The number of genes estimated for the segreganting families for both crosses were two. Qui-square data for the F2 population showed a 12:3:1 segregation, indicating dominant epistasis, with a major dominant gene and a minor gene controlling the expression of SBWMV reaction.